Evaluating the effectiveness of SADD (Students Against Driving Drunk) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University - Robertson, Leonard William (Massey University, 2003)
This research arose from a request from the New Zealand Students Against Driving Drunk (SADD) Trust. The Trust needed to have the activities of SADD evaluated for effectiveness in order to satisfy the requirements of their sponsors. SADD claims that its mission is to reduce harm amongst students by promoting alternatives to drinking and driving through positive peer influences. Drinking and driving is a risky behaviour. Substantial work has been done in the area of risk taking and driving and various methods have been used to modify adolescent risk taking behaviours. The researcher had a particular interest in the work that had been done in this regard on personality development through education. For these reasons the scope of the evaluation was expanded to include risk taking, peer influences and personality development. Three methods of data gathering were used. These included administering the Washington University Sentence Completion Test (WUSCT) of ego development on two occasions a year apart to the same students. Secondly, face to face interviews were conducted with a sample of students throughout the year 2000 and finally a written questionnaire was sent to those schools with the most active SADD groups. These three methods enabled the effectiveness of SADD to be assessed from a number of diflerent perspectives. The results obtained identified the strengths of SADD and enabled suggestions to be made for improvement in some areas. The research also identified areas in which additional research into personality development and its link with behaviour would be of value.
Keywords: New Zealand; Drunk driving; Prevention; Alcohol use; Youth